2006
DOI: 10.1002/gps.1608
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone sulfate (DHEA‐S) and Alzheimer's dementia in older subjects

Abstract: In a sample of newly-diagnosed DAT patients, we did not find significant association between presence of DAT or impairment in cognitive domains and DHEA-S levels; baseline DHEA-S levels are not associated with cumulative mortality in patients and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Despite biologic evidence for the neuroprotective effects of androgens against amyloid-β induced apoptosis and tau hyperphosphorylation, we found no association between DHEA-S and disease progression. Our findings are consistent with an earlier study in which plasma DHEA-S was not associated with presence of AD, impairment in cognitive domains, or cumulative mortality (Bo et al, 2006), albeit in contradiction to a subsequent study reporting lower plasma DHEA in AD patients respective to age-matched controls (Aldred and Mecocci, 2010). Further, DHEA levels within cerebrospinal fluid were significantly higher in AD patients compared with cognitively normal controls and correlated with Braak neuropathological disease stage.…”
Section: Discussionsupporting
confidence: 86%
“…Despite biologic evidence for the neuroprotective effects of androgens against amyloid-β induced apoptosis and tau hyperphosphorylation, we found no association between DHEA-S and disease progression. Our findings are consistent with an earlier study in which plasma DHEA-S was not associated with presence of AD, impairment in cognitive domains, or cumulative mortality (Bo et al, 2006), albeit in contradiction to a subsequent study reporting lower plasma DHEA in AD patients respective to age-matched controls (Aldred and Mecocci, 2010). Further, DHEA levels within cerebrospinal fluid were significantly higher in AD patients compared with cognitively normal controls and correlated with Braak neuropathological disease stage.…”
Section: Discussionsupporting
confidence: 86%
“…DHEA(S) concentrations are not clearly associated with cognition in dementia; however, it may be important to compare relative concentrations of DHEA-to-DHEAS and other metabolites of DHEA. Patients with Alzheimer’s disease and/or multi-infarct dementia have been reported to exhibit decreased [17; 34; 62; 91; 216; 223; 288; 304; 306; 344], as well as increased or unchanged [38; 40; 92; 172; 276; 291] plasma, serum and CSF DHEA(S) concentrations. In several instances, plasma and serum DHEA(S)-to-cortisol ratios distinguish demented participants from controls better than DHEA(S) or cortisol concentrations alone [12; 73; 170; 171; 192].…”
Section: Dhea(s) Concentrations and Neuropsychiatric Illnessesmentioning
confidence: 99%
“…Conversely, DHEAS is significantly lower in the CSF [20], but not in the serum from people affected with Alzheimer's disease in comparison to controls [12]. Although more studies are required to determine the actual status of DHEA levels in Alzheimer's disease, the majority of published studies indicated that DHEA levels were elevated in Alzheimer's disease.…”
Section: Androgens In Alzheimer's Diseasementioning
confidence: 95%
“…Many studies have confirmed that total testosterone declines at a rate between 0.9 and 1.6% per year after the third decade of life, whereas bioavailable testosterone declines at a higher annual rate due to the concurrent increase in SHBG at an average rate of approximately 1.3% per year, compounding the effect of depleting total testosterone [6][7][8][9][10][11]. DHEA and DHEAS also decline with age [12,13].…”
Section: Androgens In Normal Agingmentioning
confidence: 97%